The relations between foreign policy and defense economy in the Estado Novo period (1937-1945) - Bruna Rohr Reisdoerfer; Josiane Simão Sarti (Revista Conjuntura Austral, 2018)
The article presents the importance of the cohesion between Foreign and Defense Policies to national development in Estado Novo. In this period, this relation has developed through strong cohesion and complementarity.